Symboliczne praktyki edukacji. Doświadczenie A.S. Makarenki w postsocjalistycznym dyskursie pedagogicznym - Aleksander Połonnikow (Problemy Wczesnej Edukacji)
The problem discussed in the article is related to the attitude to the pedagogical tradition born in conditions of the formation and development of the totalitarian society. Its reconstruction and analysis is organized by denoting this experience in the form of text. In this context the relation to tradition gains an intertextual character, constructed by it being referred to the context of modernity. The key function of such contextualisaion is the so-called re-symbolization. Three strategies of resymbolization are described, namely “iconoclastic”, “iconomanic”, and “social-constructionistic”. They all, to some extent, are present in the pedagogical discourse of the post-socialist communities. The former two strategies are oriented at the “truth” of the tradition, whereas the third strategy considers is as an interpretive and practical category. Analyzed is the structural-functional organization of the three strategies of resymbolization.